A Trajetória De Raimundo Cela E A Cultura Escolar Da Enba (1910-1930) - Filha, Vera Rozane Araujo Aguiar [UNIFESP] (2017)
This dissertation discuss the trajectory of Raimundo Cela during his scholarship time in National School of Fine Arts (ENBA), at Rio de Janeiro, between 1910-1930. Cela was born in Camocim, state of Ceará, Brazil. Joined at ENBA in 1910, as a free student. In 1917, won the 24th National Exihibition of Fine Arts, for the painting The Last Dialogue of Socrates, earning the prize of foreign study in Europe. The study goes through ENBA's everyday life, analysing it's school culture, the connections among school form, norms, traditions and practices. I argue that the artistic practice of Raimundo Cela dialogues with several elements of ENBA's school culture and does not limit itself to art styles or prior concepts about art in Brazilian First Republic. I use institutional archives and Cela's personal sources to draw his trajectory at ENBA in the first decades of Twentieth-century. The study is based on the topics and methods of History and History of Art.